The connected company - Gray, David (O'Reilly, 2012)
Social networking has dramatically altered the way companies react to change. When your customers are delighted, they can amplify your message in ways that were never before possible. But when your company's performance runs short of what you've promised, customers can seize control of your brand message, spreading their disappointment and frustration faster than you can keep up. To keep pace with today's connected customers, your company must become a connected company. That means deeply engaging with workers, partners, and customers, changing how work is done, how you measure success, and how performance is rewarded. It requires a new way of thinking about your company: less like a machine to be controlled, and more like a complex, dynamic system that can learn and adapt over time. Connected companies have the advantage, because they learn and move faster than their competitors. In The Connected Company, we examine what they're doing, how they're doing it, and why it works. And we show you how your company can use the same principles to adapt - and thrive - in today's ever-changing global marketplace.
Includes bibliographical references and index. - Print version record
Keywords: Internet marketing; Marketing sur Internet